Lung Metastasis of Primary Alveolar Soft-Part Sarcoma Occurring 20 Years after Initial Treatment. (27th November 2013) - Falkenstern-Ge, R. F.; Kimmich, M.; Wohlleber, M.; Grabner, A.; Friedel, G.; Ott, G.; Leuschner, I.; Kohlhäufl, M.
Abstract : A 30-year old woman was referred to our center because of suspicion of a primary lung tumor of the right upper lobe. Histological examination of the lung lesion revealed lung metastasis of a previously treated alveolar soft part sarcoma of the musculus vastus medialis of the right femur, which was resected 20 years ago. Alveolar soft-part sarcoma is a rare malignant tumor that occurs most often in the soft tissue of lower limbs. It is a slow-growing malignant soft tissue tumor arising in muscle tissue, usually in young adults. Due to pleural and extensive mediastinal infiltration with bilateral lung metastases, a systemic treatment with chemotherapy doxorubicin and ifosfamide was initiated. Late metastases from previously treated alveolar part sarcoma should be considered in patients with suspicious lung lesions even if surgical treatment was performed a long time ago.